1997
DOI: 10.1142/s0217979297001751
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Boundary Critical Phenomena

Abstract: An introduction into the theory of boundary critical phenomena and the application of the field-theoretical renormalization group method to these is given. The emphasis is on a discussion of surface critical behavior at bulk critical points of magnets, binary alloys, and fluids. Yet a multitude of related phenomena are mentioned. The most important distinct surface universality classes that may occur for a given universality class of bulk critical behavior are described, and the respective boundary conditions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
493
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(513 citation statements)
references
References 52 publications
11
493
0
Order By: Relevance
“…It turns out that within MFT, this issue can be fully resolved in terms of a modified DA for fictitious (+, o) BCs if the location and the curvature of the actual interface at x = 0 are known. Note, however, that this mapping onto a fictitious ersatz colloid with Dirichlet BC is not expected to hold beyond MFT, because the intrinsic order parameter profile vanishes at z 0 (x) linearly ∝ z − z 0 (x), whereas at a Dirichlet wall it vanishes ∝ (z − z 0 (x)) (β 1 −β )/ν , where β 1 is a surface critical exponent (β 1 (d = 4) = 1, β 1 (d = 3) ≃ 0.8 [11]). Thus, within MFT (β 1 − β )/ν happens to be equal to 1, too, whereas in d = 3 (β 1 − β )/ν ≃ 0.8.…”
Section: B Mft Scaling Functions For An Infinitely Extended Cylindermentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that within MFT, this issue can be fully resolved in terms of a modified DA for fictitious (+, o) BCs if the location and the curvature of the actual interface at x = 0 are known. Note, however, that this mapping onto a fictitious ersatz colloid with Dirichlet BC is not expected to hold beyond MFT, because the intrinsic order parameter profile vanishes at z 0 (x) linearly ∝ z − z 0 (x), whereas at a Dirichlet wall it vanishes ∝ (z − z 0 (x)) (β 1 −β )/ν , where β 1 is a surface critical exponent (β 1 (d = 4) = 1, β 1 (d = 3) ≃ 0.8 [11]). Thus, within MFT (β 1 − β )/ν happens to be equal to 1, too, whereas in d = 3 (β 1 − β )/ν ≃ 0.8.…”
Section: B Mft Scaling Functions For An Infinitely Extended Cylindermentioning
confidence: 99%
“…These fluctuation-induced interactions can be described in terms of universal scaling functions determined by the bulk and surface universality classes of the system [9][10][11]. Simple fluids and binary liquid mixtures belong to the Ising universality class.…”
Section: Introductionmentioning
confidence: 99%
“…Among the main reasons for that rapid and successful development we can mention the interest in understanding the physics of low-dimensional systems and an immense potential of industrial applications of thin films [1][2][3]. In particular, theoretically it has been shown that systems of continuous spins (XY and Heisenberg) in two dimensions (2D) with short-range interaction cannot have long-range order at finite temperature [4].…”
Section: Introductionmentioning
confidence: 99%
“…First developed for static equilibrium bulk critical behavior, this classification scheme has subsequently been extended both to dynamic bulk critical behavior [2] as well as to static surface critical behavior of semi-infinite systems at bulk critical points [3,4].…”
mentioning
confidence: 99%
“…Owing to the O(3) symmetry, the surface of such a d=3-dimensional system cannot spontaneously order for J 1 /J < ∞. Hence the surface transition that occurs at the bulk critical point T = T c is the so-called ordinary one [4]. Its critical indices can be expressed in terms of two independent bulk exponents, e.g., η and ν, and one surface exponent, e.g., the correlation exponent η ord .…”
mentioning
confidence: 99%